2005
DOI: 10.1111/j.0014-3820.2005.tb01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Burden and Constitution of Major Histocompatibility Complex in the Malagasy Mouse Lemur, Microcebus Murinus

Abstract: We investigated the importance of the major histocompatibility complex (MHC) constitution on the parasite burden of free-ranging mouse lemurs (Microcebus murinus) in four littoral forest fragments in southeastern Madagascar. Fourteen different MHC class II DRB-exon 2 alleles were found in 228 individuals with high levels of sequence divergence between alleles. More nonsynonymous than synonymous substitutions in the functional important antigen recognition and binding sites indicated selection processes maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 65 publications
10
123
0
1
Order By: Relevance
“…In guppies, Scott (1985) found that fish previously infected with gyrodactylus were better able to combat infection, even if the previous infection had been 6 weeks prior (also see Cable and van Oosterhout 2007a). Similarly other studies have found resistance conferred by the MHC to other monogenean parasites (Ottová et al 2007), parasites in the phylum platyhelminths (Wegner et al 2003), and other parasitic worms known as helminths (Schad et al 2005). Therefore it is likely that the MHC can recognize antigens from gyrodactylus and mount a reaction using the adaptive immune system.…”
Section: Discussionmentioning
confidence: 87%
“…In guppies, Scott (1985) found that fish previously infected with gyrodactylus were better able to combat infection, even if the previous infection had been 6 weeks prior (also see Cable and van Oosterhout 2007a). Similarly other studies have found resistance conferred by the MHC to other monogenean parasites (Ottová et al 2007), parasites in the phylum platyhelminths (Wegner et al 2003), and other parasitic worms known as helminths (Schad et al 2005). Therefore it is likely that the MHC can recognize antigens from gyrodactylus and mount a reaction using the adaptive immune system.…”
Section: Discussionmentioning
confidence: 87%
“…Adaptive variability was studied in the highly polymorphic MHC-DRB exon 2 (171 bp, without primer) which includes the functionally important antigen-binding sites (ABS) (Brown et al 1988(Brown et al , 1993. The PCR amplification was carried out using the primers JS1 and JS2 as described in Schad et al (2004Schad et al ( , 2005 which were originally designed for the closely related lemur species Microcebus murinus but were also successfully applied in different rodent species (Froeschke and Sommer 2005;Harf and Sommer 2005;Meyer-Lucht and Sommer 2005). To genotype the individuals, we used single-strand conformation polymorphism analysis (SSCP) (Orita et al 1989a, b;Meyers and Bull 2002).…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…However, overdominance cannot explain all the data, and frequencydependent selection is increasingly gaining support. MHC zygosity does not appear to affect endoparasite load in certain mammals, yet specific alleles are correlated with infection status (Harf and Sommer 2005;Schad et al 2005). In Atlantic salmon, specific MHC alleles confer resistance to Aeromonas salmonicida and infectious salmon anemia virus (Grimholt et al 2003;Langefors et al 2001a).…”
Section: Introductionmentioning
confidence: 99%